2008
DOI: 10.1539/joh.l8070
|View full text |Cite
|
Sign up to set email alerts
|

Oral Toxicity of Indium in Rats: Single and 28‐Day Repeated Administration Studies

Abstract: Oral Toxicity of Indium in Rats: Single and 28-Day Repeated Administration Studies: Keiko ASAKURA, et al. Department of Preventive Medicine and Public Health, Keio University School of Medicine-Indium is widely used in the electronics industry to make semiconductors, liquid-crystal panels, and plasma display panels, and its production is increasing. However, it is necessary to handle it more cautiously than before, because the pulmonary toxicity of inhaled indium has been identified. The present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Even with the widely accepted assumption that smaller particles (i.e., nanomaterials) are more toxic, appropriate remains questionable (19). Lastly, most of toxicological data from hazard assessments to date were generated using larger particles, although indium compounds (especially indium-tin oxide) are produced at the nano-scale (2,20-24). Therefore, this study was performed to investigate the toxicity and distribution of indium compounds according to their particle size and chemical composition to fill the knowledge gap concerning the hazards of indium compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the widely accepted assumption that smaller particles (i.e., nanomaterials) are more toxic, appropriate remains questionable (19). Lastly, most of toxicological data from hazard assessments to date were generated using larger particles, although indium compounds (especially indium-tin oxide) are produced at the nano-scale (2,20-24). Therefore, this study was performed to investigate the toxicity and distribution of indium compounds according to their particle size and chemical composition to fill the knowledge gap concerning the hazards of indium compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, gastrointestinal absorption in rats was <1%. Asakura et al. (2008) observed no toxicity of indium metal administered orally to rats with a single dosage of 2 g kg −1 or a repeated oral dose of 1 g kg −1 daily for 28 d. Andersen et al.…”
Section: Indium (Z = 49)mentioning
confidence: 92%
“…In vivo, gastrointestinal absorption in rats was <1%. Asakura et al (2008) observed no toxicity of indium metal administered orally to rats with a single dosage of 2 g kg À1 or a repeated oral dose of 1 g kg À1 daily for 28 d. Andersen et al (2017) studied the invitro dissolution of indium-tin oxide (ITO) powder in a simulated gastric environment, and observed the release of <0.1% indium from the ITO powder over 4 h. After 60 d of mouse gavage with metal salts of bismuth, indium, and ruthenium, Laval et al (2018) observed similar ratios of In 3þ and Bi 3þ concentration in serum to the orally given amount. Ingested materials § All forms 0.005 * It is assumed that the bound state can be neglected for indium (i.e.…”
Section: Ingestionmentioning
confidence: 99%
“…The result of the study with rat on In metal powder [46] was considered conclusive. For the other indium compounds under consideration in the consortium, no experimental data were available, and no further animal testing was conducted.…”
Section: Selection Of Substances To Test For Acute Toxicitymentioning
confidence: 96%